The beneficial effects of citrus peel waste and its extract on fish performance and health status: A review - Kesbiç, Osman Sabri; Acar, Ümit; Mohammady, Eman Y.; Salem, Shimaa M. R.; Ragaza, Janice A.; El‐Haroun, Ehab; Hassaan, Mohamed S. (Wiley, 2022)
Food production and processing in developing countries produce a huge amount of fruit waste by-products, which is costly and pose detrimental effects on the environment. Proteins, lipids, starch, micronutrients, bioactive compounds and dietary fibres are found in many of these fruit wastes. Among fruit wastes, citrus fruits play an important role in generating a wide range of health benefits. Citrus L. of the Rutaceae family are common fruits cultivated and consumed globally both as fresh fruits and as a juice. Citrus peel wastes (CPW) are considered the main by-products, with an average of 60% of processed fruits; hence, CPW have a promising role in the food production industry. CPW contain high concentrations of polyphenol and essential oils, which have nutritional importance and pharmaceutical usage. There is a concern on the increasing prevalence and incidence of different fish infections and a growing interest in shifting from synthetic to natural antimicrobial agents, leading to the use of citrus peel wastes for identification of novel compounds for use as fish feed additives. Although the antimicrobial properties of EOs have been reviewed extensively, the antimicrobial properties of citrus peels oil have not been extensively discussed. In fish farming, feeding strategies that employ phytochemicals as modulators of immunological and physiological responses such as growth, antioxidant activity and gene expression have received attention. In the past years, several studies have reported positive results of using citrus peel extracts as a nutritional additive in aquafeeds. Recently, these dietary functional feed additives have been evaluated and reported to increase disease resistance and improve fish growth, animal welfare and feed utilization. This review elucidates the global production, bioactive compounds, natural sources, chemical structures, physical properties, practical applications of citrus peel wastes and extracts as a desirable and sustainable route in fish nutrition.
Keywords: 2. Zero hunger; 13. Climate action; 6. Clean water; 3. Good health; 12. Responsible consumption